PENERAPAN TEKNOLOGI MINI INTEGRATED FARMING SEBAGAI UPAYA PEMULIHAN EKONOMI DAN KETAHANAN PANGAN MASYARAKAT KORBAN GEMPA DI DESA ARGOREJO KECAMATAN SEDAYU KABUPATEN BANTUL - Sonita Rosningsih (Universitas Sebelas Maret, 2010)
Community service of the mini-integrated aplication program was done in the village of Argorejo, Sedayu, Bantul, Yogyakarta, on May to December 2009, aims to accelerate economic recovery and food avaibility of the earthquake-victim communities in Argorejo village. The group and individual approaches method used for implemented this program. 10 packages of local Hens and 10 packages vertikultur given to 10 selected participants (the status of young housewives) who later formed farmers' group called